Retrospective study of the efficacy of vascularized tissue transfer for treating antibiotic-resistant bacteria-infected wound: Comparison with clean and antibiotic-sensitive bacteria-infected wound. Issue 23 (11th June 2021) - Kim, Seong Hwan; Lee, Ju Ho; Kim, Seong Eun; Shin, Se Ho; Kim, Hyeon Jo; Lee, Seong Joo; Kim, Jae Hyun; Suh, In Suck
Abstract : Abstract: If wounds are infected with bacteria resistant to an empirical antibiotic regimen, effective wound treatment will be delayed. This can delay wound healing and lengthen hospital stays, increasing the costs to patients. Long-term antibiotic use can also result in minor and major complications, such as diarrhea, antibiotic resistance, or life-threatening leukopenia. Multidrug-resistant (MDR) bacteria make wound treatment even more difficult. Traditionally, surgeons thought that adequate infection control should be established before soft tissue coverage. However, wounds infected by MDR do not heal well with this traditional method and there are no optimal treatment guidelines for MDR bacteria-contaminated wounds. We reviewed 203 patients who underwent vascularized flap surgery from 2012 to 2019 to cover wounds. Class IV and I wounds were compared according to the Centers for Disease Control and Prevention classification. Class IV was further classified as antibiotic-resistant (ARB) and antibiotic-sensitive (ASB) bacteria. Wound size, mode, location, pathogens, healing time, and basic demographics were evaluated. Data were compared using Cramer's V and one-way ANOVA or independent t tests. The average healing time was longer in the ARB (19.7 [range 7–44] days) and ASB (17.9 [range 2–36] days) groups than in the Clean group (16.5 [range 7–28] days). Healing time differed in the 3 groups ( P = .036). It was longer in the class IV group than in the class I group ( P = .01). However, it was not statistically different between the ARB and ASB groups ( P  = .164). In our study the difference in healing time was small when vascularized tissue transfer was done in ARB-infected wound compared with ASB-infected and clean wound. It is necessary to perform surgery using vascularized tissue for the infected wound of antibiotic-resistant bacteria.